XXII DAE High Energy Physics Symposium Proceedings, Delhi, India, December 12 -16, 2016 (Springer Proceedings in Physics,, 2018)
These proceedings gather invited and contributed talks presented at the XXII DAE-BRNS High Energy Physics (HEP) Symposium, which was held at the University of Delhi, India, on 12-16 December 2016. The contributions cover a variety of topics in particle physics, astroparticle physics, cosmology and related areas from both experimental and theoretical perspectives, namely (1) Neutrino Physics, (2) Standard Model Physics (including Electroweak, Flavour Physics), (3) Beyond Standard Model Physics, (4) Heavy Ion Physics & QCD (Quantum Chromodynamics), (5) Particle Astrophysics & Cosmology, (6) Future Experiments and Detector Development, (7) Formal Theory, and (8) Societal Applications: Medical Physics, Imaging, etc. The DAE-BRNS High Energy Physics Symposium, widely considered to be one of the leading symposiums in the field of Elementary Particle Physics, is held every other year in India and supported by the Board of Research in Nuclear Sciences (BRNS), Department of Atomic Energy (DAE), India. As many as 400 physicists and researchers attended the 22nd Symposium to discuss the latest advances in the field. A poster session was also organized to highlight the work and findings of young researchers. Bringing together the essential content, the book offers a valuable resource for both beginning and advanced researchers in the field.